A morphometric characterization of cranial shape in terrestrial carnivorans based on fourier analysis - Pérez-Claros, Juan Antonio; Martín-Serra, Alberto; Figueirido-Castillo, Francisco Borja; Janis, Christine Marie; Palmqvist-Barrena, Carlos Paul (My University, 2013)
A number of studies have shown that skull morphology reflects the ecological adaptations of terrestrial carnivores as well as their phylogenetic legacy. Here we use Fourier shape analysis for describing the dorsal outline of the cranium in a number of extant and extinct species in the order Carnivora. To evaluate to what extent the shapes of the outlines analyzed reflect phylogeny and/or adaptation, a principal components analysis was performed with the harmonic amplitudes of the Fourier analyses. Results obtained show that cranial morphology is highly constrained by the phylogenetic legacy of each carnivoran family, as those species belonging to the same family tend to be placed in the same region of the morphospace. However, a functional signal is also present. In particular, after controlling for size effects, there is a weak but significant correlation between an axis of morphological variation and the estimates of bite force at the level of the upper canine, while another independent axis is related to bite force measurements at the carnassial. The wide distribution of canids in the empirical morphospace reflects their ecological disparity, while the restricted dispersal on the plot of saber-tooth predators probably results from biomechanical constraints posed by their highly specialized, hypertrophied upper canines. Moreover, there is a general allometric trend for all carnivoran families, which is associated with the lateral expansion of the zygomatic arches, and two different allometric trends exclusive to canids and felids, respectively, which are linked to snout length. Our results show that phylogeny constrains to a large extent the morphological adaptive zone which carnivoran species can inhabit.
Keywords: Fourier, Análisis de; Carnívoros - Morfología; Fourier analysis; Morphometric characterization; Terrestrial carnivorans